2015
DOI: 10.7863/ultra.15.14.10055
|View full text |Cite
|
Sign up to set email alerts
|

B‐Lines in Assessment of Pulmonary Hypertension in Patients With Interstitial Lung Diseases

Abstract: ulmonary hypertension is a common and important complication of interstitial lung diseases, which substantially affects the exercise tolerance and survival of patients with these diseases. Right heart catheterization is the reference standard for measurement of pulmonary artery (PA) pressure; however, it is an invasive technique and is not always performed for patients with interstitial lung diseases. Transthoracic echocardiography is a useful technique for noninvasive estimation of PA pressure 1,2 through tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Previous literature has reported that the number of pulmonary ultrasound B lines is highly correlated with the severity of pulmonary edema 19,20 . There was also a positive correlation between pulmonary B lines with pulmonary artery pressure 21 . However, newborn infants' lung volume and coastal space were small, and the number of lung B lines was sometimes difficult to distinguish and accurately count.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous literature has reported that the number of pulmonary ultrasound B lines is highly correlated with the severity of pulmonary edema 19,20 . There was also a positive correlation between pulmonary B lines with pulmonary artery pressure 21 . However, newborn infants' lung volume and coastal space were small, and the number of lung B lines was sometimes difficult to distinguish and accurately count.…”
Section: Discussionmentioning
confidence: 97%
“…19,20 There was also a positive correlation between pulmonary B lines with pulmonary artery pressure. 21 However, newborn infants' lung volume and coastal space were small, and the number of lung B lines was sometimes difficult to distinguish and accurately count. The proposal of LUS provides quantitative indicators for clinical practice, which could reflect the more comprehensive and systematic nature and severity of lung lesions.…”
Section: Comparison Of Pulmonary Artery Pressure Lung Score and Dd-te...mentioning
confidence: 99%
“…And previous studies had applied CPUS to analyze the relationship between B-line and pulmonary artery pressure in patients with interstitial pulmonary disease. The result had shown that the number of B-line was positively correlated with the systolic pulmonary artery pressure [29]. In this study, we used CPUS to monitoring disease progression and curative effect in rat model of monocrotaline-induced PAH.…”
Section: Cardiopulmonary Ultrasoundmentioning
confidence: 99%